Human-computer interaction. advanced interaction modalities and techniques : 16th International Conference, HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings, Part II - Kurosu, Masaaki (Lecture Notes in Computer Science, 2014)
The 3-volume set LNCS 8510, 8511 and 8512 constitutes the refereed proceedings of the 16th International Conference on Human-Computer Interaction, HCII 2014, held in Heraklion, Crete, Greece in June 2014. The total of 1476 papers and 220 posters  presented at the HCII 2014 conferences was carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas.